-6x-2y=-4

Simple and best practice solution for -6x-2y=-4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6x-2y=-4 equation:


Simplifying
-6x + -2y = -4

Solving
-6x + -2y = -4

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '2y' to each side of the equation.
-6x + -2y + 2y = -4 + 2y

Combine like terms: -2y + 2y = 0
-6x + 0 = -4 + 2y
-6x = -4 + 2y

Divide each side by '-6'.
x = 0.6666666667 + -0.3333333333y

Simplifying
x = 0.6666666667 + -0.3333333333y

See similar equations:

| 2+2f=8 | | 4(x-1)=2(3y-1) | | 200m-100m+57900=60300-200m | | .23+480.48=x | | M-3n+5= | | 9p^2(p+1)=4(p+1)-9(p+1) | | 4y+11=79 | | 4.75m+15=3m+24+m-4 | | 203.75/(-0.1)= | | .5n=3n-20 | | 5(x+9)-4=5 | | y7+6=11 | | 2x+4=2x+4.000000000000000000000000000000000000000000000000000000001 | | 4y-7=39 | | 0.5n-5=3n-25 | | 2x-5=39(7+2x) | | 2sin(x)-4-cos(x)=0 | | 6u-6=-9(u-1) | | ifBC=RLthen | | 36+12m^2+m^4=0 | | 4a*3a= | | ln(6x+2)=ln(3x-19) | | -4.3-3z-2.9-z=-3z+5.7 | | -8m-8n+p-2=-10n-9p+8 | | 12*x^2-4=0 | | t(2t+-1)=1 | | 10-(4x-1)=8-5x | | 7x+21(2x-3)=180 | | 8c*3c= | | 3x+22x-4=5(5x+6) | | (-7b+4a)+(-6a-9b)= | | 5w^2+39w+5y=0 |

Equations solver categories